Use of ultrasonic dual-mode mixing for graphene infusion to make hybrid GFRPs: Study on mechanical performance. (April 2022) - Choudhury, Pannalal; Halder, Sudipta; Das, Subhankar
Optimized process parameters of a top–down approach via the ultrasonic dual-mode mixing process are adopted to disperse and exfoliate graphene nanoplatelets uniformly in the epoxy resin and fabricate hybrid GFRP laminates. The in-plane tensile and out-of-plane flexural behavior of the hybrid GFRPs made with different concentration of GNPs have been investigated. The test results show that ∼39.47% and ∼40.87% enhancement in tensile strength and flexural strength has been attained for the hybrid GFRPs made with 1 wt% of GNPs. In addition, the enhancement of ∼117% in absorbed failure energy and ∼28.56% in work of fracture is also achieved. Mori Tanaka Method has been used to calculate the modulus of the GNP-epoxy composite system, and these results are used further to predict the modulus of the hybrid GFRPs. The theoretical moduli so obtained are used to compare the experimental modulus of the hybrid GFRPs as a function of GNP concentration. Fractography examination of the fractured hybrid GFRPs reveals it reduced interlaminar delamination, which is governed by the effective load transferability of GNP-infused epoxy network.